Tensões contemporâneas no processo de passagem da educação infantil para o ensino fundamental: um estudo de caso - Vanessa Ferraz Almeida Neves (2010)
I investigated the transition of a group of children from preschool to elementary school in Belo Horizonte, considering the context of the new legislation in education. The processes of data collection and analysis were guided by the sociology of childhood (CORSARO, 2005) and by an interactional ethnographic perspective (CASTANHEIRA, CRAWFORD, DIXON and GREEN, 2001). Data sources included field notes, videotape records of classrooms lives, audiotape records of semi-structured and informal interviews of teachers, children, and written artifacts used and/or produced in the classrooms. I searched for an understanding of the multiplicity of contexts influencing the everyday life of the classrooms: peer culture, school and teachers culture, and the educational system. Therefore, it is understood that local contexts are influenced by global contexts.The educational practices that were central in both preschool and elementary school were related to play and literacy, although different in each one of the classrooms. I argue that the lack of dialogue in the Brazilian educational system regarding early childhood and elementary education was reflected upon the process of rupture experienced by the children in their transition from preschool to elementary school. The research, focusing on the childrens perspective, evidenced that it is necessary a closer integration between literacy and play in both preschool and elementary school: both dimensions are fundamental to childrens lives, inside and outside of schools.